2021
DOI: 10.3389/fimmu.2021.648216
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Activation Profiles of Mucosal-Associated Invariant T Cells in Patients With Tuberculosis and HIV in a High Endemic Setting

Abstract: Background: MAIT cells are non-classically restricted T lymphocytes that recognize and rapidly respond to microbial metabolites or cytokines and have the capacity to kill bacteria-infected cells. Circulating MAIT cell numbers generally decrease in patients with active TB and HIV infection, but findings regarding functional changes differ.Methods: We conducted a cross-sectional study on the effect of HIV, TB, and HIV-associated TB (HIV-TB) on MAIT cell frequencies, activation and functional profile in a high TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…MAIT cells are T cells that are similarly non-classically restricted but with a propensity for mucosal homing, recognizing antigens presented on MR1 with rapid response capabilities and the functional capacity to kill infected cells ( 296 , 427 , 428 ). However, their active role is somewhat confusing as some clinical data demonstrate that individuals with TB have decreased numbers of circulating MAIT cells with reduced activation ( 429 ), whereas others are detected with tetramers at similar frequencies in peripheral blood from TB-infected and uninfected individuals ( 427 ). In mouse models of TB challenge, MAIT cells have been shown to delay T-cell priming early during challenge but are efficient targets of host-directed therapies ( 428 ), making them an interesting target in vaccine and drug therapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…MAIT cells are T cells that are similarly non-classically restricted but with a propensity for mucosal homing, recognizing antigens presented on MR1 with rapid response capabilities and the functional capacity to kill infected cells ( 296 , 427 , 428 ). However, their active role is somewhat confusing as some clinical data demonstrate that individuals with TB have decreased numbers of circulating MAIT cells with reduced activation ( 429 ), whereas others are detected with tetramers at similar frequencies in peripheral blood from TB-infected and uninfected individuals ( 427 ). In mouse models of TB challenge, MAIT cells have been shown to delay T-cell priming early during challenge but are efficient targets of host-directed therapies ( 428 ), making them an interesting target in vaccine and drug therapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death 1 (PD-1) and GrB were higher than their preinfection rate ( Lal et al., 2020 ). The longer the course of the disease, the more irreversibly damaged the immune function of MAIT cells becomes; in addition, their immune response and function against other pathogens, such as Mycobacterium tuberculosis, are significantly reduced ( Balfour et al., 2021 ).…”
Section: Biological Characteristics Of Mait Cellsmentioning
confidence: 99%
“…A rather surprising outcome from another study showed that priming MAIT cells with 5-OP-RU in Mtbinfected rhesus macaques did not lead to expansion of the population, failed to stimulate cytokine production, and instead upregulated programmed death-1 (PD-1), normally associated with T cell exhaustion [88]. This dramatic reduction in circulating MAIT cell is also witnessed with HIV infection and HIV-TB coinfection and importantly, these numbers do not recover despite successful treatment, conceivably influencing the ability to withstand future opportunistic infections [59,89]. This suggests that MAIT cell replenishment could be a useful strategy to prevent disease relapse or other secondary infections.…”
Section: Mait Cell Directed Therapy and Tb Infectionmentioning
confidence: 99%